2010
DOI: 10.1016/j.ijporl.2010.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Auditory neuropathy spectrum disorder in late preterm and term infants with severe jaundice

Abstract: Objective-To evaluate if severe jaundice is associated with acute auditory neuropathy spectrum disorder in otherwise healthy late preterm and term neonates.Methods-In a prospective observational study, all neonates who were admitted with severe jaundice at which exchange transfusion may be indicated as per American Academy of Pediatrics guidelines had comprehensive auditory evaluation performed before discharge to home. Neonates with infection, perinatal asphyxia, chromosomal disorders, craniofacial malformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 32 publications
4
62
3
3
Order By: Relevance
“…3 Individuals with ANSD may or may not be deaf. 22 They have abnormal auditory nerve function but normal cochlear function; they therefore have abnormal results on auditory brainstem response testing but normal results on otoacoustic emission testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Individuals with ANSD may or may not be deaf. 22 They have abnormal auditory nerve function but normal cochlear function; they therefore have abnormal results on auditory brainstem response testing but normal results on otoacoustic emission testing.…”
Section: Discussionmentioning
confidence: 99%
“…22 They have abnormal auditory nerve function but normal cochlear function; they therefore have abnormal results on auditory brainstem response testing but normal results on otoacoustic emission testing. 3 Children with ANSD may be at increased risk of having language and speech impairments. 22 Notably, several studies have shown that hyperbilirubinemia-associated abnormalities in brainstem auditory evoked responses may be reversible with treatment of hyperbilirubinemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty percent of infants with admission RR AABR converted to bilateral pass, whereas 22 infants had persistent RR AABR confirmed to be auditory neuropathy by diagnostic audiology procedures. [17][18][19] All infants with maximum TSB ,31 mg/dL and BIND score #3 had normal auditory function at follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…A diagnostic evaluation for auditory neuropathy [17][18][19] was performed if the AABR screen was RR at 3 to 5 months. Compliance with follow-up appointments was 74.5%.…”
Section: Outcome Definitionsmentioning
confidence: 99%